Strengthening ASEAN-US Relations: Korean Peninsula as Conduit? - Ho, Shawn (2017)
Much attention has been paid to how the recently concluded 30th ASEAN Summit in Manila has dealt with the South China Sea disputes. Now is perhaps the time for ASEAN to strengthen its regional security credentials by paying more attention to the challenge on the Korean Peninsula.